Kepuasan Kerja, Motivasi Kerja, dan Disiplin Kerja Dalam Meningkatkan Kinerja Pegawai - Meilia Angelina; Indra Supriadi (Papanda Publisher, 2023)
Employees are an important element that determines the progress of an organization or company. The success of the company is very dependent on the performance of its employees. Therefore, companies must create human resources capable of producing optimal performance. Research seeks to reveal the performance of employees of a company which is determined by several factors, including job satisfaction, work motivation and work discipline. This study aims to determine the effect of job satisfaction, work motivation and work discipline on the performance of employees of a company. This research is a quantitative research. This research was conducted at PT. Borwita Citra Prima Surabaya with a sample of 80 respondents. The research instrument used a questionnaire with a Likert scale of 1-6. This study shows that job satisfaction, work motivation, and work discipline simultaneously affect employee performance. The three independent variables together are able to influence the dependent variable. If an agency can provide job satisfaction supported by good work motivation and work discipline, then all three will affect employee performance together. Thus job satisfaction with the support of work motivation and good work discipline will affect employee performance.